A History of Drug‐Induced Torsades de Pointes Is Associated With T‐wave Morphological Abnormalities. Issue 6 (25th October 2017) - Bhuiyan, Tanveer A.; Graff, Claus; Kanters, Jørgen K.; Melgaard, Jacob; Toft, Egon; Kääb, Stefan; Struijk, Johannes J.
Abstract : The hypothesis of the study is that Torsades de pointes (TdP) history can be better identified using T‐wave morphology compared to Fridericia‐corrected QT interval (QTcF) at baseline. ECGs were recorded at baseline and during sotalol challenge in 20 patients with a history of TdP (+TdP) and 16 patients without previous TdP (–TdP). The QTcF and T‐wave morphology combination score (MCS) were calculated. At baseline, there was no significant difference in QTcF between the groups (+TdP: QTcF = 446 ± 9 ms; –TdP: QTcF = 431 ± 9 ms, P  = 0.27). In contrast, MCS was significantly different between the groups at baseline (+TdP: MCS = 1.07 ± 0.095; –TdP: MCS = 0.74 ± 0.07, P  = 0.012). Both QTcF and MCS could be used to discriminate between +TdP and –TdP after sotalol but only MCS reached statistical significance at baseline. Combining QTcF with MCS provided a significantly larger difference between groups than QTcF alone.